Description of MSME Survey in Viet Nam - de Brauw, Alan; Ceballos, Francisco; Le, Ly; Soneja, Payal (International Food Policy Research Institute, 2023)
During the first half of 2023, researchers associated with Work Package 2 (WP2) of the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT) conducted three linked surveys to learn more about micro, small, and medium enterprises (MSMEs) that currently supply foods within urban, peri-urban, and rural locations in Viet Nam and contribute to developing ways to foster their supply of sustainable nutritious foods. 1 Therefore, the surveys had three linked goals—to better characterize the business environment in which MSMEs operate; to understand any constraints they face in selling more sustainable nutritious foods; and to help inform interventions with scaling potential that could increase the availability of sustainable nutritious foods for consumers. The first survey was a listing exercise (or a short audit, as it is called by Work Package 1 of SHiFT). This listing exercise was almost exclusively an observational exercise, taking place within selected areas of the urban, peri-urban, and rural sites. The idea was to understand the proportion of different types of businesses available, what was sold at those businesses, and to understand if people could sit down at the establishment or not (particularly for restaurants). The second survey was a longer survey targeting outlets from the listing exercise that had a higher chance of being MSMEs and could potentially modify their food offerings. This MSME survey inquired about labor use, sources of foods or ingredients for foods sold, asset holdings of the business, access to and use of financial instruments, degree of formality, and perceptions of and desire to sell more sustainable nutritious foods. The MSME survey, in turn, was used to seed a third survey, targeted at suppliers, with the objective of identifying any potential constraints at the supplier level for expanding the offering of sustainable nutritious foods. Outlets participating in the MSME survey were asked to share the contact information of some of their suppliers, and a subset of these were reached by phone and administered a reduced version of the MSME questionnaire, inquiring about their businesses and perceptions. A secondary goal of the survey was to understand to what extent employment of women and youth relates to MSME activity. In particular, when devising interventions to help MSMEs offer more sustainable nutritious foods, we want to ensure that those interventions have either a positive or neutral effect on employment among women and youth; in other words, we want to ensure that they do not have a negative effect on employment among these populations.